Speech Act Analysis of Teacher Talk in EFL Classroom - Nurul Arifah; Kisman Salija; Abdullah Abdullah (ARRUS Journal of Social Sciences and Humanities, 2024)
This research aimed to classify the structural forms of utterances in locutionary acts, illocutionary acts types, and the impacts of perlocutionary acts on the students in EFL (English as a Foreign Language) classrooms. This research used qualitative research to analyze the data. The subject of this research is a teacher who actively teaches in the English and Literature Department, at Universitas Islam Negeri Alauddin Makassar. Data were collected through observation checklists in the classroom and semi-structured interview with the teacher. The results showed that based on finding by Yule’s theory, the researcher found three forms of locutionary acts used by the teacher in the teaching and learning process, such as declarative form, imperative form, and interrogative form. Second, based on Searle’s theory, the researcher found the types of illocutionary acts produced by teachers during the teaching and learning process, namely representative (explaining, informing, announcing), directive (commanding, requesting, asking, suggesting), expressive (greetings, thanking, praising), and commissive (assuring, undertaking, promising). Third, based on the utterances performed by the teacher in the EFL classroom process, the researcher found perlocutionary acts such as the students asking questions, and doing something. The research concluded that language has a function in the speech act especially for facilitating communication skills of language learning and shaping the classroom dynamic.